A high frequency AC heater based on switched capacitors for lithium-ion batteries at low temperature. (October 2021) - Zhang, Yuanxi; Yang, Yaning; Shang, Yunlong; Cui, Naxin
Highlights: A high frequency AC heater based on two switched capacitors is proposed. A optimization method based on PSO algorithm is introduced to optimize the heating frequency. The heating results are validated under different heating frequencies and different SOC. Fast heating speed and less cell energy loss are realized without external energy supply. Abstract: Lithium-ion batteries suffer from significant performance deterioration at subzero temperatures, which brings difficulty to the promotion of electric vehicles. In this paper, a high frequency alternating current (AC) heater based on switched capacitors is proposed which can heat batteries with fast speed and good uniformity without external energy supply. The optimal heating frequency is determined based on particle swarm optimization to obtain the fastest heating speed. The proposed heating topology only needs one pair of pulse width modulation signals to drive four MOSFETs to circulate an alternating current between the batteries and switched capacitors, leading to easy control with simple structure and low cost. The effectiveness of the proposed AC heater is validated under different heating frequencies at initial temperature −20°C and –25°C, respectively. Experimental results show that by circulating an alternating current with the optimal heating frequency of 10 kHz, the proposed heater can heat lithium-ion batteries from -20°C to 0°C within 2.2min, consuming only 5.4% cell energy, and can heat lithium-ion batteries from -25°C to 0°C within 9 min, consuming only 7.8% cell energy.